Optimization of a Long Wavelength Vertical-Cavity Surface- Emitting Lasers by Employing Photonic Crystal - Marjani, Saeid; Marjani, Hamid (Asian Journal of Chemistry, 2012)
In this work, we attempt to design, simulate and characterize a GaAs-based high power long wavelength vertical-cavity surface-emitting lasers by employing combined single defect photonic crystal index guiding layer and oxide layer. In this way, increases the optical wavelength from 1.541 μm to 1.568 μm and the lasing power 85.382 % from 11.349 mW to 21.039 mW at a bias current of 35 mA. The device employs InGaAsP active region, which is sandwiched between GaAs/AlGaAs and GaAs/AlAs distributed Bragg reflectors. The basic design goal was to obtain vertical-cavity surface-emitting laser with the high power, high slop efficiency for L-band optical fiber application. This paper provides key results of the device characteristics, including the optical wavelength, the output power and threshold current.